INCOME ANALYSIS OF LAYER CHICKEN FARMER WITH PARTNERSHIP SYSTEM AT FARMER GROUP LAMONGGEDO JAYA IN SUB-DISTRICT BARUGA KENDARI CITY - Sri, Helmina; Sani, La Ode Arsad; Rahman, Rahman; Munadi, Laode Muh (Pascasarjana Universitas Sulawesi Tenggara, 2021)
This study aimed to analyze the income of layer chicken farmer with partnership system at Lamonggedo Jaya farmer group. This study was conducted in Sub-district Baruga, Kendari City on January 2017. Materials used in this study were layer chicken. Location of this research was determined by purposive sampling based on consideration that farmer group Lamonggedo Jaya has population of layer chicken in laying phase as many as 4,609 chickens. Research variables were production cost (cage, breed, feed, medicine, vaccine, employee, electric, and water) and income source (egg and natural fertilizer). Data were collected and tabulated, then analyzed qualitatively and quantitatively by using the formula = TR-TC. Result of the study showed that income of layer chicken farmer at farmer group Lamonggedo Jaya was Rp. 9.215.